RACISM IN 12 YEARS A SLAVE MOVIE - Muhammad Taufik; Hasniar Hasniar (UIN Alauddin Makassar, 2016)
AbstractThis jurnal studied about racial injustice in 12 Years a Slave movie. This research is to find out the kinds and impacts of racial injustice in 12 Years a Slave movie. This research used descriptive qualitative and used theories of Paradies et al. and Liliweri to analysis the kinds of racial injustice and used theory of Utsey et al. to analysis the impacts of racial injustice. The data collections of this research are script and film 12 Years a Slave movie, which is released in 2013. In collecting data, the writer used note taking as the instrument to find out the kinds and impacts of racial injustice in these movies. In this research, the writer found out that there are twenty-eight data of kinds racial injustice which is divided into five, they were; prejudice, stereotype, discrimination, violence, segregation and seven data of impacts of racial injustice, which is divided into three, they were; racism-related trauma, racism-related stress and distress, anticipatory racism reaction. In addition, the writer found that only violence kinds of racial injustice that had impact in these movie. Based on the findings and discussions, the writer concluded that racial injustice is the action of White people that threaten physical/mentally and unfair action that disadvantages to Black people.AbstrakRasisme dalam Film 12 Tahun menjadi budak. Jurnal ini belajar tentang ketidakadilan rasial dalam film 12 tahun menjadi budak budak. Penelitian ini bertujuan untuk mencari tahu jenis dan dampak dari ketidakadilan rasial film 12 tahun menjadi budak budak. Penelitian ini menggunakan deskriptif kualitatif dengan menggunakan teori Paradies et al. dan Liliweri untuk menganalisa jenis-jenis ketidakadilan rasial dan digunakan teori dari Utsey et al. analisis dampak ketidakadilan rasial. Dalam pengumpulan data berdasarkan pada manuskrip film 12 tahun menjadi budak budak, yang dirilis pada tahun 2013. Dalam pengumpulan data, penulis peneliti menggunakan note taking sebagai instrument. Hasilnya, peneliti menemukan bahwa terdapat 28 jenis ketidakadilan rasial yang dibagi ke dalam lima kategori yakni; prasangka, stereotip, diskriminasi, kekerasan, pemisahan. Sedangkan dampak ketidakadilan rasial, terbagi ke dalam tiga kategori, keduanya; rasisme yang berhubungan dengan trauma, rasisme yang berhubungan dengan stres dan tekanan, serta rasisme antisipatif reaksi. Olehnya itu, penulis menemukan bahwa kekerasan ketidakadilan rasial terdapat dalam film ini. Dari hasil temuan, penulis menyimpulkan bahwa ketidakadilan rasial adalah tindakan yang dilakukan oleh orang kulit putih yang mengancam fisik/mental dan tindakan yang tidak adil dengan menindas orang kulit hitam.